Effects of immunomodulation in classic infantile Pompe patients with high antibody titers - Poelman, E. (Orphanet J Rare Dis, 2019)
PURPOSE: To evaluate whether immunomodulation can eliminate high sustained antibody levels, and thereby improve clinical outcome in classic infantile Pompe patients receiving enzyme replacement therapy (ERT) with recombinant human alpha-glucosidase (rhGAA). METHODS: Three patients (two cross-reactive immunologic material (CRIM) negative) with high sustained antibodies received a three-week treatment protocol with Rituximab and Bortezomib, followed by daily Rapamycin and monthly IVIG. Patients received 40 mg/kg/week rhGAA. Antibody titers were measured using ELISA. Neutralizing effects on cellular uptake were determined. Clinical efficacy was measured in terms of (ventilator-free) survival, reduction in left ventricular mass index (LVMI) and improvement in motor function. RESULTS: Before immunomodulation anti-rhGAA antibody titers ranged from 1:156,250 to 1:781,250 and at last assessment from 1:31,250 to 1:156,250. Neutralizing effects of anti-rhGAA antibody titers (observed in two patients) disappeared. Infusion-associated reactions were no longer present. Immunomodulation resulted in substantial increases of aspartate transaminase, alanine transaminase, and creatine kinase levels. The two CRIM-negative patients who could walk at start of immunomodulation maintained their ability to walk; the patient who had lost this ability did not regain it. CONCLUSIONS: To some extent, the immunomodulation protocol used in our study reduced antibody titers, but it did not eliminate them. Overall, there have been few reports on secondary immunomodulation, and various protocols have been applied. Future research should seek to identify the most successful immunomodulation protocol in patients with high sustained titers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13023-019-1039-z) contains supplementary material, which is available to authorized users.